Allium cepa Linn Improved Rhodanese Activity and Half-life of Cyanide in the Blood - Ola-Mudathir, Fausat Kikelomo (Current Advances in Chemistry and Biochemistry Vol. 8, 2021)
Rhodanese is an intramitochondrial liver enzyme that detoxifies cyanide. Allium cepa (Onion); rich in organosulphur may provide sulphur for the detoxification of cyanide. The possible effects of Allium cepa on rhodanese activity during cyanide toxicity was investigated in vitro and in vivo in male Wistar rats. In vivo experiments studied the effects of methanol extract of onion (MEAC) and sodium thiosulphate (Na2S2O3) on rhodanese activity, urine thiocyanate concentration and effects of MEAC, raw onion and Na2S2O3 on half-life of potassium cyanide (KCN). In vitro experiments studied the effects of MEAC and essential oil of onion on rhodanese activities in the liver cells. Results of the in vivo study revealed that administration of Na2S2O3 in the cyanide treated group enhance activity of rhodanese, while the extract did not enhance it. The results of the in vitro study showed that essential oil of onion increased rhodanese activity 10 fold that of the extract. The half-life of KCN was significantly lower (p<0.05) with consumption of raw onion when compared with control. The results suggest that Allium cepa enhance cyanide detoxification by enhancing rhodanese enzyme activity and by reducing the half-life of cyanide in the blood.